“To the Interests and Conscience of the Great Mass of the Community:” The Evolution of Temperance Societies in Nineteenth-Century Central Canada - Ferry, Darren (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2003)
AbstractThe resilience of nineteenth-century temperance societies as a cultural force in central Canada is a testament to their adaptability towards shifting societal trends, as well as their ability to utilize diverse strategies in the war against the liquor traffic. And yet the inclusive appeal of these organizations among all members of the community masked the conflicts and contentions found within the temperance movement. Pre-Confederation temperance societies established a large constituency of support culled from middle-class evangelicals and the skilled working class, although the measured withdrawal from the benefit system of mutual aid eroded the enthusiasm of skilled workers for temperance societies. However, the sectarian and political turmoil from within temperance associations clearly resulted in the irrelevance of temperance societies by mid-century. While temperance societies experienced a marked escalation in influence by the last two decades of the nineteenth century, a divergent approach taken by rural and urban temperance advocates in relation to legislative prohibition led to more discord and disagreements over the ultimate direction of the temperance movement. The openness of late nineteenth-century temperance societies was once again exposed as empty rhetoric, as the spectre of prohibition became a political hurdle too strong for a divided temperance community to overcome.